Disclosable Restructuring Paper - Niger - GPE - Support to Quality Education Project - P132405 - Mulet, Pamela (2018)
The development objective of the GPE - Support to Quality Education Project for Niger is to improve access to schooling, retention of students in school, and the quality of theteaching and learning environment at the basic education level, in the Republic of Niger.The proposed restructuring includes (i) an extension of the project closing date by 9 months to June 30, 2019, (ii) a reallocation of funds between components and disbursement categories, (iii) updated disbursement estimates, and (iv) changes to the end target dates in the Results Framework to account for the project extension.
Keywords: openalex:import